(untitled) (Journal of Technology Research, 2025)
Crack resistance in asphalt mixtures is a vital element for extending the lifespan of pavements and improving road quality. This research aims to study the effect of aging and polymer addition on crack resistance in asphalt mixtures using the Semi-Circular Bend (SCB) test. Asphalt samples were prepared and cut according to test requirements, then subjected to various aging conditions. The results showed that increasing the depth of the crack leads to a significant reduction in indirect tensile strength, regardless of the aging condition. The study also observed that aging enhances the stiffness and brittleness of the asphalt, increasing the likelihood of cracking. The use of appropriate additives is deemed essential for improving the performance of mixtures and extending their lifespan. The study emphasizes the importance of conducting regular tests and continuous maintenance of pavements, as well as the necessity of increasing the number of samples in laboratory experiments to achieve higher statistical accuracy, particularly when examining the effects of aging and different temperatures. The results highlight the significance of the SCB test as an effective tool for assessing crack resistance and stress the need to consider aging and additives to improve the long-term durability of roads.